Besøk på sykehjem. En kvantitativ studie av sykehjemsbeboeres besøkshyppighet - Galek, Joanna; Simonsen, Morten; Grov, Ellen-Karine; Sandvoll, Anne Marie (Nordisk tidsskrift for helseforskning, 2018)
Social contact is essential for the well-being of the nursing home residents.Visiting frequency in nursing homes is rarely investigated. The purpose of this study was to map the number of visits for nursing home residents. Nursing students collected data during their nursing home practice. 355 residents were included in this cross-sectional study. We explored the association between visit frequency and age, gender, type of department, activities of daily living (ADL) and length of stay. Data was analyzed using statistical analysis. The average number of visits was 8,8 per month. However, there were differences in visit frequency among the 15 institutions. Residents in the long-term department received fewer visits compared to the dementia and short-term department. Significant correlations between ADL function, gender, length of stay, age and frequency of visits were not found. More research to identify causes for the differences in visit frequency between different institutions is needed. Keywords: nursing homes; visiting; visit frequency; sykehjem; besøk; besøkshyppighet